Invariance compensation PID control for a proportional valve-controlled asymmetric cylinder system - Wenbin Xu; Le Zeng (Advances in Mechanical Engineering)
A load flow model of a proportional valve-controlled asymmetric cylinder system is developed to assess inconsistent dynamic properties. The load flow property is analyzed, and the basic state is defined for the system. In addition, an invariance compensation method that considers the structure and load effect is proposed. Any asymmetric state of the system is equivalent to the basic state through invariance compensation, then the symmetrical load flow property is obtained, which is verified through simulation. Proportion–integration–differentiation (PID) control based on invariant compensation is used in the system, and the dynamic characteristics are almost the same. The experimental results show that the compensation control based on the invariance principle can better realize the symmetric load flow characteristics of the system within a certain range of load pressures. And the displacement responses employing invariance compensation PID control under various loads indicate that the asymmetric characteristics of the system can be basically eliminated, so the consistency of the forward and reverse responses and stability of the system are improved significantly.